ANALISIS PENERAPAN MEDIA PAPAN PECAHAN SEBAGAI ALAT BANTU VISUAL DALAM PEMAHAMAN MATERI PECAHAN SISWA KELAS IV - Ainur Rodhiyah; Bambang Edi Siswanto (PHI: Jurnal Pendidikan Matematika, 2026)
This study aims to analyze the application of fraction boards as a visual aid to improve fourth-grade students' understanding of fractions. The research approach used was qualitative research with descriptive analysis, focusing on an in-depth description of the learning process and student responses to the use of fraction boards. Data collection techniques included observation, student questionnaires, and documentation to obtain comprehensive information regarding student interest, ease of understanding, and engagement during learning. The results showed that 75% of students strongly agreed that the fraction boards helped them understand fraction concepts, particularly numerators and denominators. Furthermore, 60–70% of students stated that learning became more engaging and enjoyable. Therefore, it can be concluded that the use of fraction boards is highly effective in improving students' understanding of fraction concepts and is able to create a more engaging, interactive, and enjoyable learning environment. This media has proven to be a powerful alternative visual aid in mathematics learning, particularly for fourth-grade students on fractions.